Pengetahuan Dan Tindakan Penderita Tb Paru Tentang Teknik Dan Tujuan Batuk Efektif Untuk Bersihan Jalan Nafas - Batubara, Khairunnisa (Jurnal Studi Keperawatan, 2025)
Effective coughing is a method of coughing correctly, where the client can save energy so that he does not get tired easily and can expel phlegm optimally. Effective coughing technique is an action taken to clear secretions from the respiratory tract. The aim of an effective coughing technique is to expel phlegm attached to the throat, dilute phlegm, reduce shortness of breath due to phlegm accumulation, increase oxygen levels in the body, facilitate clearing of the respiratory tract, avoid splashes of phlegm. This research uses a "Descriptive Survey" research design and the research method is a Cross Sectional approach. The total population in this study was 22 people suffering from pulmonary TB in the UPTD work area of the Sei Kepayang Community Health Center. The sampling technique used the Saturated Sampling technique, meaning that the entire population was sampled, so the total sample was 22 respondents. Based on the results of research on the knowledge and actions of pulmonary TB sufferers regarding effective coughing techniques and goals for clearing the airway, the knowledge level was 4.76 (68%) in the "good" category, the action level was 4.16 (59.4%) with the "sufficient" category, the results of knowledge and actions of pulmonary TB sufferers regarding techniques and goals are 63.7% in the sufficient category. It is recommended that pulmonary TB sufferers always use effective coughing techniques when coughing, so that sufferers can expel phlegm easily.